THE ANALYSIS OF PARAGRAPH ELEMENTS IN EDITORIAL OF THE JAKARTA POST - Widya Akhira; Jufri Jufri (English Language and Literature, 2018)
This paper discusses the elements of the paragraph in the editorial in Jakarta Post. Jakarta Post is one of the newspapers in Indonesia. The Jakarta Post is a daily English daily newspaper in Indonesia. The Jakarta Post started as a collaboration between four media in Indonesia by urging the Information Minister and politicians. The first edition was printed on April 25, 1983, spending several years with minimal advertising and increasing circulation. After a change in editor-in-chief in 1991, the Jakarta Post began to take a more vocal pro-democracy standpoint. For the validity of this paper, the analysis of the paper is published officially on legitimate online websites. In analyzing the data, I found some of the most frequently mentioned paragraph elements in the editorial. In Jakarta Post's most frequently published editorial is Minor Detail with frequency of 57 times (48%). While Major Detail appears 28 times (24%), then Topic Sentence appears 25 times (21%) and Thesis Statement appears 8 times (7%).